Penggunaan Aplikasi Photomath pada Limit Aljabar di MAS Plus Al Ulum Medan: Pengabdian - Hetty Elfina; Dede Ibrahim Muthawali; Khotna Sofiyah; Suci Dahlya Narpila; Syarif Hidayat Matondang; Elia Elfani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service aims to improve the understanding of students of class XI Religious Sciences at MAS Plus Al Ulum Medan on algebraic limit material through the use of Photomath application. This activity was carried out in April 2025 with a total of 32 participants. The implementation method consisted of training on the use of Photomath application, group discussions, and independent exercises carried out for 2 days. Data were collected through questionnaires to find out how much the Photomath application can affect learning in the classroom and an early-late test to see the improvement of learning outcomes by using the Photomath application. Based on the results of the activity, it shows that the use of Photomath application can improve the understanding of the concept of limit algebra, help students follow the steps of solving systematically, and create a more pleasant learning atmosphere. Students' learning outcomes increased from an average student score of 58 to an average student score of 86. The questionnaire results obtained data that 85% of students felt more confident in working on limit problems and 78% of students stated that math learning became more fun.